Design and fabrication of Surface Acoustic Wave resonators on Lithium Niobate - Sidek, Fatini; Ramli, Noor Amalina; Nordin, Anis Nurashikin; Voiculescu, Ioana (2010)
Surface Acoustic Wave (SAW) resonators are essential components in communication devices and are used mainly as oscillators, frequency synthesizers and transceivers. Common piezoelectric substrates are quartz, Lithium Tantalate (LiTaO3) and Lithium Niobate (LiNbO3). In this paper we describe the design and fabrication of SAW resonators on LiNbO3. The design of the SAW resonators was simulated using COMSOL MultiphysicsTM. Two SAW resonators with resonance frequency of 218 MHz with varying number of reflectors were fabricated and measured. Measurements conducted using an RF Probe station and network analyzer yielded losses of -48.3 dB and -49.32 dB for Resonator 1 and Resonator 2 respectively.